IPS TEACHER RECEPTION ON THE IMPLEMENTATION OF FACE-TO-FACE LEARNING (PTM) DURING THE COVID-19 PANDEMIC - Syaharuddin Syaharuddin; Ridho Hayati; Bambang Subiyakto; A. Munaya Rahman; mutiani mutiani (Universitas Lambung Mangkurat, 2022)
Face-to-face learning (PTM) during the pandemic does not provide comfort for students and social studies teachers in learning at school. Learning requires students and teachers to strictly carry out PROKES, from wearing masks to not being allowed to gather. In addition to students, teachers face the same problem when required to complete curriculum targets (emergency) with shorter study times. The aims of this study are to (1) describe the implementation of learning during a pandemic; (2) the constraints experienced during the implementation of PTM during the pandemic; (3) Implementation of PTM which is expected to overcome the obstacles faced during the pandemic. The subjects of this study were principals, teachers and students in the city of Banjarmasin as many as 37 people. Structured interviews were conducted via google form. Data were analyzed by following the Miles and Huberman models. This article concludes that the choice of learning methods with PTM in the midst of a pandemic, according to students the most important thing is that it is easier to accept lessons and more effective communication with fellow friends and teachers. Social studies teachers are easier to condition the class so that the material that has been prepared is easier to convey. The main obstacle for PTM is the shorter study time so that the curriculum targets are difficult to achieve. Second, the difficulty of communicating between students and teachers because they have to carry out strict PROKES both in the use of masks and prohibition of gathering. This study recommends a more comprehensive investigation of the implementation of PTM in order to find the right formulation for the implementation of PTM to run effectively.